2009
DOI: 10.1111/j.1538-7836.2009.03588.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between circulating antibodies against domain I of beta2‐glycoprotein I and thrombosis: an international multicenter study

Abstract: Summary. Background: Diagnosis of the antiphospholipid syndrome (APS) is difficult as a result of limited specificity of existing assays for detecting clinically relevant antiphospholipid antibodies. Anti-beta2-glycoprotein I (beta2GPI) antibodies play a central role in the disease process of APS. Objectives: We have investigated the relation between antiphospholipid antibodies with specificity for domain I of beta2GPI and thrombosis/pregnancy morbidity in an international multicenter study. Patients/methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
217
8
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(248 citation statements)
references
References 20 publications
15
217
8
3
Order By: Relevance
“…1(A)], 14 whereas it interacts with pathogenic aAbs by the N-terminal domain (DmI). 4,15 Of note, high plasma levels of anti-b2GpI…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(A)], 14 whereas it interacts with pathogenic aAbs by the N-terminal domain (DmI). 4,15 Of note, high plasma levels of anti-b2GpI…”
Section: Introductionmentioning
confidence: 99%
“…5 b2GpI is now recognized as the major autoantigen involved in APS, 3,6 and the presence of anti-b2GpI Abs strongly correlates with the occurrence of thrombotic events in APS patients. 4,7 The mature sequence of human b2GpI consists of 326 amino acids with four N-linked carbohydrate chains, 8,9 localized in the third and fourth domain (see below) and accounting for about 19% of the protein mass (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, autoantibodies against b2GPI consist of heterogeneous populations including subclasses directed against various epitopes of the molecule . Only the subpopulation that recognizes specific epitopes on domain I of b2GPI showed a good correlation with thrombosis and pregnancy morbidity (de Laat et al, 2006(de Laat et al, , 2009. Interestingly, Colasanti et al (2012) proposed a novel pathogenic mechanism in which autoantibodies specific to a peptide of the b2GPI domain I, which shares 88% identity with an epitope of human TLR4 and is present in serum from APS and SLE patients, are able to directly engage human TLR4 in b2GPI-independent manner, inducing a pro-inflammatory phenotype in ECs and monocytes.…”
Section: Open Questionsmentioning
confidence: 99%
“…In circular b2GPI, the epitopes for the autoantibodies interacts with domain V of the same molecule. After binding to anionic surfaces, b2GPI changes conformation, thus exposing the hidden epitopes recognizable by the autoantibodies in the APS, especially the cryptic epitope (Gly40-Arg43) on the domain I of b2GPI, which is recognized by anti-b2GPI antibodies (de Laat et al, 2006(de Laat et al, , 2009.…”
Section: B2-glycoprotein I (B2gpi) and Its Receptors On The Cell Surfacementioning
confidence: 99%
“…Another multicenter study from the same group reported that 55% of patients with various autoimmune diseases, all positive for anti-b 2 GPI, had anti-domain I antibodies. 89 These patients had an odds ratio of 3.5 for thrombosis compared to those without anti-domain 1 antibodies. Additionally, they found that anti-domain I antibodies were associated with pregnancy morbidity.…”
Section: The Epitopes Of Apl and Treatment Outcomementioning
confidence: 99%